If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(t + -2) + -1r = 4 Reorder the terms: 7(-2 + t) + -1r = 4 (-2 * 7 + t * 7) + -1r = 4 (-14 + 7t) + -1r = 4 Reorder the terms: -14 + -1r + 7t = 4 Solving -14 + -1r + 7t = 4 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '14' to each side of the equation. -14 + -1r + 14 + 7t = 4 + 14 Reorder the terms: -14 + 14 + -1r + 7t = 4 + 14 Combine like terms: -14 + 14 = 0 0 + -1r + 7t = 4 + 14 -1r + 7t = 4 + 14 Combine like terms: 4 + 14 = 18 -1r + 7t = 18 Add '-7t' to each side of the equation. -1r + 7t + -7t = 18 + -7t Combine like terms: 7t + -7t = 0 -1r + 0 = 18 + -7t -1r = 18 + -7t Divide each side by '-1'. r = -18 + 7t Simplifying r = -18 + 7t
| 6x^3+19x^2+8x-5=0 | | 6x^3+19x^2+8x=5 | | 2(5r-4)=12r | | 5(2+n)=0 | | 30=12b | | 5r+25=31+5r | | 2g-13h+15=x | | (5x-38)=(3x-4) | | 4(x-1)+6=2x-5(1+x) | | -3x+3+7x=-13 | | 2/3x-5=20 | | 11y-1=5.75 | | (1/3)(27) | | 2.49(n+1.24)=11.17 | | 10y+10+5x=180 | | -2-2/3=12 | | 4.23-7.2x=3.6x-9 | | -2(3x+5)+4x=4 | | -12+4x=7x+17 | | -100(m-80)=4 | | (2x-5)+(4x+6)= | | 9x+44=9x-44 | | 6*-4+24= | | 6x+12y=288 | | 4=5x+3-5x | | -12790+185t=0 | | 82=2x-6 | | 4=5x+3+5x | | 2.5-8(1-5a)=-20.5 | | 4-6y=13 | | 3y-3x=-6 | | -8(3f+9)=18-5f |